Meningkatkan literasi keuangan digital pada pelaku UMKM melalui sosialisasi gerakan nasional non-tunai - Rohmini Indah Lestari; Djoko Santoso; Indarto Indarto (University of Islam Malang, 2021)
The Covid-19 pandemic is a milestone for the Gerakan Nasional Non-Tunai (GNNT) in Indonesia. This GNNT socialization activity to Micro, Small, and Medium Enterprises (MSMEs) aimed to support the Indonesia Payment System Blueprint (BSPI) 2025. MSMEs are the largest business (98.67%) which contributes 60.34% to Gross Domestic Product (GDP) in Indonesia. The socialization, MSME actors can make transactions with the electronic leisure payment system. Electronic payments as a result of buying and selling transactions electronically through the internet (e-commerce). The method of implementing this activity is to conduct socialization and Forum Group Discussions (FGD) face-to-face under health protocol standards during the Covid-19 pandemic. In addition to socialization, e.g. of the application of using electronic money through smartphones was also given. The enthusiasm of the participants was shown during the discussion session. They feel that they understand more about the benefits of the electronic payment system in the GNNT policy and will apply it to their productive economic business activities. After receiving the socialization, we have recorded that three of the eight micro-business actors participating in the socialization applied the non-cash transactions. Warung Kamu had applied the payment using the Quick Response Code Indonesia Standard (QRIS). The Olahan Bandeng and Ida Collection market their products through the Kopimi E-Gerai.